“Punk rock is also for fagots”: punk aesthetics in Bruce Labruce’s queer cinema - Reis, Vinícius Antônio Batista (Revista do Colóquio, 2024)
This work aims to draw parallels between the visual construction of queer cinema and punk aesthetics, seeking to understand the aspects that construct the visual issue of the film “Raspberry Reich” (Bruce LaBruce, 2004), which is part of the queercore movement, founded by himself LaBruce.
Keywords: Punk; Queer; Bruce LaBruce; Post-Pornography; Queercore